Pressure-sensitive conductive rubber particle and preparation method thereof
By using ethylene propylene rubber and ethylene propylene rubber blended with ethylene propylene rubber and adding porous polyaniline doped with modified tin dioxide nanoparticles, the problem of the conductive rubber material being difficult to take into account high elasticity, heat resistance and oxidation resistance while maintaining the conductive properties, achieving high conductivity and good physical and mechanical properties.
Patent Information
- Application Number
- CN202410929893.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-11
- Publication Date
- 2025-04-25
AI Technical Summary
It is difficult for existing conductive rubber materials to maintain their conductive properties while taking into account high elasticity, heat resistance and oxidation resistance.
The blended rubber of ethylene propylene rubber and ethylene propylene rubber are used as the matrix, and porous polyaniline doped with modified tin dioxide nanoparticles are added thereto, and the pressure-sensitive conductive rubber particles are formed by vulcanization treatment.
It realizes the high conductivity, good physical and mechanical properties and oxidation resistance of conductive rubber materials, and improves the overall performance of the material.
Smart Images

Figure BDA0004939319400000131
Abstract
Description
Technical Field
[0001] The invention relates to the field of rubber materials, and in particular to pressure-sensitive conductive rubber particles and a preparation method thereof. Background Art
[0002] Rubber is a polymer compound with good mechanical properties and processing properties. It is also heat-resistant, oil-resistant, and corrosion-resistant. It has good applications in the fields of medical treatment, transportation, construction, machinery, electronics, etc. Rubber itself is an insulating material. By adding conductive fillers to rubber and distributing the conductive fillers throughout the rubber matrix to form a conductive network, a composite rubber material can be obtained. On the basis of maintaining the high elasticity and flexibility of the rubber itself, the rubber has good conductive properties and its application range is broadened. Conductive rubber can be divided into conductive rubber for electromagnetic shielding, antistatic rubber, pressure-sensitive conductive rubber, etc. according to product use. Commonly used rubber matrices include natural rubber, silicone rubber, ethylene propylene rubber, and rubber blends. Different rubber matrices are usually selected according to different uses. Among them, blended rubber is a rubber with a proper amount of another rubber added to obtain different types of rubbers with their own excellent properties. It currently occupies a dominant position in the rubber industry and is also well used in conductive rubber. Conductive fillers are mainly divided into two categories: carbon-based and metal-based. Carbon-based conductive fillers mainly include graphite, carbon black, carbon fiber, etc. Metal-based conductive fillers mainly include metal powders such as gold, silver, copper, and metal oxides. Traditional conductive fillers have their own advantages and disadvantages. By modifying or compounding conductive fillers, conductive fillers with excellent comprehensive performance can be obtained, so that rubber can obtain better conductive properties. Summary of the invention
[0003] Technical problem to be solved: The technical problem to be solved by the present invention is to provide a pressure-sensitive conductive rubber particle.
[0004] Technical solution: A pressure-sensitive conductive rubber particle, comprising the following components in weight ratio: EPDM rubber: 50-60 parts; EPDM rubber: 40-50 parts; Porous polyaniline doped with modified tin dioxide nanoparticles: 30-60 parts; Stearic acid: 0.5-1.5 parts; Zinc oxide: 4-6 parts; Diisopropyl peroxide: 2-4 parts; Antiaging agent RD: 1-2 parts; Paraffin oil: 8-10 parts. Preferably, the method for preparing the porous polyaniline doped with modified tin dioxide nanoparticles comprises the following steps: S11. The modified tin dioxide nanoparticles are added to water and ultrasonically dispersed to obtain a uniform aqueous dispersion; S12. The aniline monomer is dissolved in toluene as the oil phase, the aqueous dispersion is used as the aqueous phase, the aqueous phase and the oil phase are mixed, and emulsified with a high-speed emulsifier to obtain an emulsion; S13. The emulsion was diluted with deionized water, ammonium persulfate was dissolved in a hydrochloric acid solution, both were placed in an ice water bath, the hydrochloric acid solution containing ammonium persulfate was slowly dripped into the emulsion, and the ice water bath was maintained until the reaction was completed; S14. The reaction product is dialyzed and freeze-dried to obtain porous polyaniline doped with modified tin dioxide nanoparticles. Preferably, in step S13, the molar ratio of aniline monomer to ammonium persulfate is 1:0.8-1.2. Preferably, the volume proportion of the modified tin dioxide nanoparticles in the porous polyaniline doped with modified tin dioxide nanoparticles is 75-85%. Preferably, the modified tin dioxide nanoparticles are Ce-doped tin dioxide nanoparticles. Preferably, the preparation method of the modified tin dioxide nanoparticles is a chemical coprecipitation method, comprising the following steps: S21. The tin chloride and cerium chloride were added to deionized water and stirred to dissolve to obtain a mixed solution; S22. Slowly adding aqueous ammonia to the mixed solution until pH = 9 to 10 and stirring to obtain a uniformly dispersed Ce / Sn co-precipitated hydroxide; S23. The obtained reactant is filtered, washed, dried, ground and calcined to obtain Ce-doped tin dioxide nanoparticles. Preferably, in step S21, the molar ratio of Ce / Sn is 1:2.5-4. Preferably, the calcination temperature in step S23 is 750-800°C. Preferably, the method for preparing the rubber particles comprises the following steps: S1. Mixing: The EPDM rubber and the EPDM rubber are placed on an open mill for mixing, and the porous polyaniline doped with modified tin dioxide nanoparticles, stearic acid, zinc oxide, antioxidant RD, diisostyrene peroxide and paraffin oil are added in proportion and mixed evenly to obtain a mixed rubber; S2. Vulcanization: Put the mixed rubber into a vulcanizer for vulcanization to obtain vulcanized rubber; S3. Molding: Put the vulcanized rubber into the extruder, cut and collect it after extrusion to obtain pressure-sensitive conductive rubber particles. Beneficial effects: Compared with the prior art, the present invention has the following characteristics: The conductive rubber of the present invention is a porous polyaniline prepared by adding modified tin dioxide nanoparticles to a blended rubber of EPDM rubber and EPDM rubber. The blended rubber matrix has excellent comprehensive performance, the modified tin dioxide nanoparticles have good conductivity, and the porous polyaniline has good bonding with the rubber matrix after being compounded. Both EPDM rubber and EPDM rubber have high saturation, and both have good antioxidant and corrosion resistance. EPDM rubber has excellent heat resistance, and EPDM rubber has good mechanical and physical properties. The two have similar structures and good compatibility, and both can be vulcanized with peroxides. The blending of the two can form a high-density cross-linked network, so that the rubber matrix has excellent comprehensive performance. Metal oxides are ceramic materials with low cost and stable chemical properties. As fillers, they can improve the mechanical properties of rubber, but their disadvantage is that they have poor electrical conductivity. Using chemical doping to modify the surface of metal oxides can effectively improve the electrical conductivity of metal oxides and make them conductive fillers for rubber. Pure tin dioxide, as a semiconductor oxide, is an important functional material. By doping with rare earth Ce, the concentration of carriers can be increased and its conductivity can be improved. At the same time, rare earth oxides can act as dispersants and inhibit grain growth, making the nanoparticles fine and uniform in size. Polyaniline is a conductive polymer material with good electrical conductivity and stable electrochemical properties. The modified tin dioxide nanoparticles are compounded with polyaniline and a porous structure is prepared. The bonding strength between the nanoparticles and the rubber matrix can be enhanced without affecting the conductivity of the nanoparticles. At the same time, the metal oxides can improve the mechanical properties of the matrix. Compared with the prior art, the present invention has the following advantages and positive effects: The invention uses EPDM rubber and EPDM rubber blended rubber, which improves the physical and mechanical properties of the rubber while ensuring its excellent heat resistance and oxidation resistance, and the rubber matrix has excellent comprehensive performance. The invention adds modified tin dioxide nanoparticles, and rare earth doping can effectively improve the conductivity of metal oxides and refine the grains at the same time, and the preparation method is simple and low in cost. The present invention utilizes conductive polymer polyaniline to compositely modify tin dioxide nanoparticles, the conductive filler has good bonding with the silica gel matrix, and both the conductivity and stability are improved. DETAILED DESCRIPTION In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. Specific preferred examples are as follows: Embodiment 1: A pressure-sensitive conductive rubber particle, comprising the following components in weight ratio: EPDM rubber: 60 parts; EPDM rubber: 40 parts; Porous polyaniline doped with modified tin dioxide nanoparticles: 60 parts; Stearic acid: 0.5 parts; Zinc oxide: 6 parts; Diisopropyl peroxide: 2 parts; Anti-aging agent RD: 2 parts; Paraffin oil: 8 parts; The method for preparing the porous polyaniline doped with modified tin dioxide nanoparticles comprises the following steps: S11. The modified tin dioxide nanoparticles are added to water and ultrasonically dispersed to obtain a uniform aqueous dispersion; S12. The aniline monomer is dissolved in toluene as the oil phase, the aqueous dispersion is used as the aqueous phase, the aqueous phase and the oil phase are mixed, and emulsified with a high-speed emulsifier to obtain an emulsion; S13. The emulsion was diluted with deionized water, ammonium persulfate was dissolved in a hydrochloric acid solution, both were placed in an ice water bath, the hydrochloric acid solution containing ammonium persulfate was slowly dripped into the emulsion, and the ice water bath was maintained until the reaction was completed; S14. dialyzing the reaction product and freeze-drying it to obtain porous polyaniline doped with modified tin dioxide nanoparticles; In step S13, the molar ratio of aniline monomer to ammonium persulfate is 1:0.8; The volume proportion of the modified tin dioxide nanoparticles in the porous polyaniline doped with modified tin dioxide nanoparticles is 75%; the modified tin dioxide nanoparticles are Ce-doped tin dioxide nanoparticles; The preparation method of the modified tin dioxide nanoparticles is a chemical coprecipitation method, comprising the following steps: S21. The tin chloride and cerium chloride were added to deionized water and stirred to dissolve to obtain a mixed solution; S22. Slowly adding aqueous ammonia to the mixed solution until pH = 9 and stirring to obtain uniformly dispersed Ce / Sn co-precipitated hydroxide; S23. The resulting reactant was filtered, washed, dried, ground and calcined to obtain Ce-doped tin dioxide nanoparticles; In step S21, the molar ratio of Ce / Sn is 1:2.5; The calcination temperature in step S23 is 750° C. The method for preparing the rubber particles comprises the following steps: S1. Mixing: EPDM rubber and EPDM rubber were placed on an open mill and mixed for 1 min, porous polyaniline doped with modified tin dioxide nanoparticles was added in proportion and mixed for 3 min, stearic acid, zinc oxide, antioxidant RD, diisostyrene peroxide and paraffin oil were added and mixed for 3 min, the mixing temperature was 70 ° C, and a mixed rubber was obtained; S2. Vulcanization: The mixed rubber is placed in a vulcanizer for vulcanization at a vulcanization temperature of 160°C to obtain a vulcanized rubber; S3. Molding: Put the vulcanized rubber into an extruder at an extrusion temperature of 80°C, cut and collect after extrusion to obtain pressure-sensitive conductive rubber particles. Embodiment 2: A pressure-sensitive conductive rubber particle, comprising the following components in weight ratio: EPDM rubber: 50 parts; EPDM rubber: 50 parts; Porous polyaniline doped with modified tin dioxide nanoparticles: 30 parts; Stearic acid: 1.5 parts; Zinc oxide: 4 parts; Diisopropyl peroxide: 4 parts; Anti-aging agent RD: 1 part; Paraffin oil: 10 parts; The method for preparing the porous polyaniline doped with modified tin dioxide nanoparticles comprises the following steps: S11. The modified tin dioxide nanoparticles are added to water and ultrasonically dispersed to obtain a uniform aqueous dispersion; S12. The aniline monomer is dissolved in toluene as the oil phase, the aqueous dispersion is used as the aqueous phase, the aqueous phase and the oil phase are mixed, and emulsified with a high-speed emulsifier to obtain an emulsion; S13. The emulsion was diluted with deionized water, ammonium persulfate was dissolved in a hydrochloric acid solution, both were placed in an ice water bath, the hydrochloric acid solution containing ammonium persulfate was slowly dripped into the emulsion, and the ice water bath was maintained until the reaction was completed; S14. dialyzing the reaction product and freeze-drying it to obtain porous polyaniline doped with modified tin dioxide nanoparticles; In step S13, the molar ratio of aniline monomer to ammonium persulfate is 1:1.2; The volume proportion of the modified tin dioxide nanoparticles in the porous polyaniline doped with modified tin dioxide nanoparticles is 85%; the modified tin dioxide nanoparticles are Ce-doped tin dioxide nanoparticles; The preparation method of the modified tin dioxide nanoparticles is a chemical coprecipitation method, comprising the following steps: S21. The tin chloride and cerium chloride were added to deionized water and stirred to dissolve to obtain a mixed solution; S22. Slowly adding aqueous ammonia to the mixed solution until pH = 10 and stirring to obtain a uniformly dispersed Ce / Sn co-precipitated hydroxide; S23. The resulting reactant is filtered, washed, dried, ground and calcined to obtain Ce-doped tin dioxide nanoparticles; In step S21, the Ce / Sn molar ratio is 1:4; The calcination temperature in step S23 is 800° C. The method for preparing the rubber particles comprises the following steps: S1. Mixing: EPDM rubber and EPDM rubber were placed on an open mill and mixed for 2 min, porous polyaniline doped with modified tin dioxide nanoparticles was added in proportion and mixed for 2 min, stearic acid, zinc oxide, antioxidant RD, diisostyrene peroxide and paraffin oil were added and mixed for 2 min, the mixing temperature was 100 ° C, and a mixed rubber was obtained; S2. Vulcanization: The mixed rubber is placed in a vulcanizer for vulcanization at a vulcanization temperature of 180°C to obtain a vulcanized rubber; S3. Molding: Put the vulcanized rubber into an extruder at an extrusion temperature of 120°C, cut and collect after extrusion to obtain pressure-sensitive conductive rubber particles. Embodiment 3: A pressure-sensitive conductive rubber particle, comprising the following components in weight ratio: EPDM rubber: 53 parts; EPDM rubber: 47 parts; Porous polyaniline doped with modified tin dioxide nanoparticles: 42 parts; Stearic acid: 1.2 parts; Zinc oxide: 4.5 parts; Diisopropyl peroxide: 3.5 parts; Antiaging agent RD: 1.4 parts; Paraffin oil: 9 parts; The method for preparing the porous polyaniline doped with modified tin dioxide nanoparticles comprises the following steps: S11. The modified tin dioxide nanoparticles are added to water and ultrasonically dispersed to obtain a uniform aqueous dispersion; S12. The aniline monomer is dissolved in toluene as the oil phase, the aqueous dispersion is used as the aqueous phase, the aqueous phase and the oil phase are mixed, and emulsified with a high-speed emulsifier to obtain an emulsion; S13. The emulsion was diluted with deionized water, ammonium persulfate was dissolved in a hydrochloric acid solution, both were placed in an ice water bath, the hydrochloric acid solution containing ammonium persulfate was slowly dripped into the emulsion, and the ice water bath was maintained until the reaction was completed; S14. dialyzing the reaction product and freeze-drying it to obtain porous polyaniline doped with modified tin dioxide nanoparticles; In step S13, the molar ratio of aniline monomer to ammonium persulfate is 1:1; The volume proportion of the modified tin dioxide nanoparticles in the porous polyaniline doped with modified tin dioxide nanoparticles is 82%; the modified tin dioxide nanoparticles are Ce-doped tin dioxide nanoparticles; The preparation method of the modified tin dioxide nanoparticles is a chemical coprecipitation method, comprising the following steps: S21. The tin chloride and cerium chloride were added to deionized water and stirred to dissolve to obtain a mixed solution; S22. Slowly adding aqueous ammonia to the mixed solution until pH = 9.7 and stirring to obtain a uniformly dispersed Ce / Sn co-precipitated hydroxide; S23. The resulting reactant is filtered, washed, dried, ground and calcined to obtain Ce-doped tin dioxide nanoparticles; In step S21, the Ce / Sn molar ratio is 1:3; The calcination temperature in step S23 is 785°C; The method for preparing the rubber particles comprises the following steps: S1. Mixing: EPDM rubber and EPDM rubber were placed on an open mill and mixed for 2 min, porous polyaniline doped with modified tin dioxide nanoparticles was added in proportion and mixed for 3 min, stearic acid, zinc oxide, antioxidant RD, diisostyrene peroxide and paraffin oil were added and mixed for 2 min, the mixing temperature was 90 ° C, and a mixed rubber was obtained; S2. Vulcanization: The mixed rubber is placed in a vulcanizer for vulcanization at a vulcanization temperature of 175°C to obtain vulcanized rubber; S3. Molding: Put the vulcanized rubber into an extruder at an extrusion temperature of 110°C, cut and collect after extrusion to obtain pressure-sensitive conductive rubber particles. Embodiment 4: A pressure-sensitive conductive rubber particle, comprising the following components in weight ratio: EPDM rubber: 52 parts; EPDM rubber: 48 parts; Porous polyaniline doped with modified tin dioxide nanoparticles: 50 parts; Stearic acid: 0.7 parts; Zinc oxide: 5.6 parts; Diisopropyl peroxide: 2.4 parts; Antiaging agent RD: 1.7 parts; Paraffin oil: 10 parts; The method for preparing the porous polyaniline doped with modified tin dioxide nanoparticles comprises the following steps: S11. The modified tin dioxide nanoparticles are added to water and ultrasonically dispersed to obtain a uniform aqueous dispersion; S12. The aniline monomer is dissolved in toluene as the oil phase, the aqueous dispersion is used as the aqueous phase, the aqueous phase and the oil phase are mixed, and emulsified with a high-speed emulsifier to obtain an emulsion; S13. The emulsion was diluted with deionized water, ammonium persulfate was dissolved in a hydrochloric acid solution, both were placed in an ice water bath, the hydrochloric acid solution containing ammonium persulfate was slowly dripped into the emulsion, and the ice water bath was maintained until the reaction was completed; S14. dialyzing the reaction product and freeze-drying it to obtain porous polyaniline doped with modified tin dioxide nanoparticles; In step S13, the molar ratio of aniline monomer to ammonium persulfate is 1:0.9; The volume proportion of the modified tin dioxide nanoparticles in the porous polyaniline doped with modified tin dioxide nanoparticles is 77%; the modified tin dioxide nanoparticles are Ce-doped tin dioxide nanoparticles; The preparation method of the modified tin dioxide nanoparticles is a chemical coprecipitation method, comprising the following steps: S21. The tin chloride and cerium chloride were added to deionized water and stirred to dissolve to obtain a mixed solution; S22. Slowly adding aqueous ammonia to the mixed solution until pH = 9.2 and stirring to obtain a uniformly dispersed Ce / Sn co-precipitated hydroxide; S23. The resulting reactant is filtered, washed, dried, ground and calcined to obtain Ce-doped tin dioxide nanoparticles; In step S21, the Ce / Sn molar ratio is 1:3.5; The calcination temperature in step S23 is 760°C; The method for preparing the rubber particles comprises the following steps: S1. Mixing: EPDM rubber and EPDM rubber were placed on an open mill and mixed for 1 min, porous polyaniline doped with modified tin dioxide nanoparticles was added in proportion and mixed for 2 min, stearic acid, zinc oxide, antioxidant RD, diisostyrene peroxide and paraffin oil were added and mixed for 3 min, the mixing temperature was 80 ° C, and a mixed rubber was obtained; S2. Vulcanization: The mixed rubber is placed in a vulcanizer for vulcanization at a vulcanization temperature of 165°C to obtain a vulcanized rubber; S3. Molding: Put the vulcanized rubber into an extruder at an extrusion temperature of 90°C, cut and collect after extrusion to obtain pressure-sensitive conductive rubber particles. Embodiment 5: A pressure-sensitive conductive rubber particle, comprising the following components in weight ratio: EPDM rubber: 55 parts; EPDM rubber: 45 parts; Porous polyaniline doped with modified tin dioxide nanoparticles: 37 parts; Stearic acid: 1.0 part; Zinc oxide: 5.1 parts; Diisopropyl peroxide: 2.9 parts; Antiaging agent RD: 1.6 parts; Paraffin oil: 8 parts; The method for preparing the porous polyaniline doped with modified tin dioxide nanoparticles comprises the following steps: S11. The modified tin dioxide nanoparticles are added to water and ultrasonically dispersed to obtain a uniform aqueous dispersion; S12. The aniline monomer is dissolved in toluene as the oil phase, the aqueous dispersion is used as the aqueous phase, the aqueous phase and the oil phase are mixed, and emulsified with a high-speed emulsifier to obtain an emulsion; S13. The emulsion was diluted with deionized water, ammonium persulfate was dissolved in a hydrochloric acid solution, both were placed in an ice water bath, the hydrochloric acid solution containing ammonium persulfate was slowly dripped into the emulsion, and the ice water bath was maintained until the reaction was completed; S14. dialyzing the reaction product and freeze-drying it to obtain porous polyaniline doped with modified tin dioxide nanoparticles; In step S13, the molar ratio of aniline monomer to ammonium persulfate is 1:1.1; The volume proportion of the modified tin dioxide nanoparticles in the porous polyaniline doped with modified tin dioxide nanoparticles is 80%; the modified tin dioxide nanoparticles are Ce-doped tin dioxide nanoparticles; The preparation method of the modified tin dioxide nanoparticles is a chemical coprecipitation method, comprising the following steps: S21. The tin chloride and cerium chloride were added to deionized water and stirred to dissolve to obtain a mixed solution; S22. Slowly adding aqueous ammonia to the mixed solution until pH = 9.4 and stirring to obtain a uniformly dispersed Ce / Sn co-precipitated hydroxide; S23. The resulting reactant is filtered, washed, dried, ground and calcined to obtain Ce-doped tin dioxide nanoparticles; In step S21, the Ce / Sn molar ratio is 1:3; The calcination temperature in step S23 is 790°C; The method for preparing the rubber particles comprises the following steps: S1. Mixing: EPDM rubber and EPDM rubber were placed on an open mill and mixed for 2 min, porous polyaniline doped with modified tin dioxide nanoparticles was added in proportion and mixed for 3 min, stearic acid, zinc oxide, antioxidant RD, diisostyrene peroxide and paraffin oil were added and mixed for 2 min, the mixing temperature was 100 ° C, and a mixed rubber was obtained; S2. Vulcanization: The mixed rubber is placed in a vulcanizer for vulcanization at a vulcanization temperature of 170°C to obtain a vulcanized rubber; S3. Molding: Put the vulcanized rubber into an extruder at an extrusion temperature of 100°C, cut and collect after extrusion to obtain pressure-sensitive conductive rubber particles. Comparative Example 1: A rubber particle comprising the following components by weight: EPDM rubber: 57 parts; EPDM rubber: 43 parts; Porous polyaniline doped with modified tin dioxide nanoparticles: 10 parts; Stearic acid: 0.8 parts; Zinc oxide: 5 parts; Diisopropyl peroxide: 3 parts; Antiaging agent RD: 1.5 parts; Paraffin oil: 9 parts; The method for preparing the porous polyaniline doped with modified tin dioxide nanoparticles comprises the following steps: S11. The modified tin dioxide nanoparticles are added to water and ultrasonically dispersed to obtain a uniform aqueous dispersion; S12. The aniline monomer is dissolved in toluene as the oil phase, the aqueous dispersion is used as the aqueous phase, the aqueous phase and the oil phase are mixed, and emulsified with a high-speed emulsifier to obtain an emulsion; S13. The emulsion was diluted with deionized water, ammonium persulfate was dissolved in a hydrochloric acid solution, both were placed in an ice water bath, the hydrochloric acid solution containing ammonium persulfate was slowly dripped into the emulsion, and the ice water bath was maintained until the reaction was completed; S14. dialyzing the reaction product and freeze-drying it to obtain porous polyaniline doped with modified tin dioxide nanoparticles; In step S13, the molar ratio of aniline monomer to ammonium persulfate is 1:1; The volume proportion of the modified tin dioxide nanoparticles in the porous polyaniline doped with modified tin dioxide nanoparticles is 83%; the modified tin dioxide nanoparticles are Ce-doped tin dioxide nanoparticles; The preparation method of the modified tin dioxide nanoparticles is a chemical coprecipitation method, comprising the following steps: S21. The tin chloride and cerium chloride were added to deionized water and stirred to dissolve to obtain a mixed solution; S22. Slowly adding aqueous ammonia to the mixed solution until pH = 9 and stirring to obtain uniformly dispersed Ce / Sn co-precipitated hydroxide; S23. The resulting reactant was filtered, washed, dried, ground and calcined to obtain Ce-doped tin dioxide nanoparticles; In step S21, the Ce / Sn molar ratio is 1:4; The calcination temperature in step S23 is 775°C; The method for preparing the rubber particles comprises the following steps: S1. Mixing: EPDM rubber and EPDM rubber were placed on an open mill and mixed for 1 min, porous polyaniline doped with modified tin dioxide nanoparticles was added in proportion and mixed for 2 min, stearic acid, zinc oxide, antioxidant RD, diisostyrene peroxide and paraffin oil were added and mixed for 2 min, the mixing temperature was 85 ° C, and a mixed rubber was obtained; S2. Vulcanization: The mixed rubber is placed in a vulcanizer for vulcanization at a vulcanization temperature of 160°C to obtain a vulcanized rubber; S3. Molding: Put the vulcanized rubber into an extruder at an extrusion temperature of 105°C, cut and collect after extrusion to obtain rubber particles. Comparative Example 2: A rubber particle comprising the following components by weight: EPDM rubber: 59 parts; EPDM rubber: 41 parts; Polyaniline doped with modified tin dioxide nanoparticles: 54 parts; Stearic acid: 1.1 parts; Zinc oxide: 4.2 parts; Diisopropyl peroxide: 3.8 parts; Antiaging agent RD: 1.2 parts; Paraffin oil: 8 parts; The preparation method of the polyaniline doped with modified tin dioxide nanoparticles comprises the following steps: S11. The modified tin dioxide nanoparticles are added to water and ultrasonically dispersed to obtain a uniform aqueous dispersion; S12. The aniline monomer is dissolved in toluene as the oil phase, the aqueous dispersion is used as the aqueous phase, the aqueous phase and the oil phase are mixed, and emulsified with a high-speed emulsifier to obtain an emulsion; S13. The emulsion is diluted with deionized water, ammonium persulfate is dissolved in a hydrochloric acid solution, both are placed in an ice water bath, the hydrochloric acid solution containing ammonium persulfate is slowly dripped into the emulsion, and the ice water bath is maintained until the reaction is completed to obtain polyaniline doped with modified tin dioxide nanoparticles; In step S13, the molar ratio of aniline monomer to ammonium persulfate is 1:0.9; The volume proportion of the modified tin dioxide nanoparticles in the polyaniline doped with modified tin dioxide nanoparticles is 79%; The modified tin dioxide nanoparticles are Ce-doped tin dioxide nanoparticles; The preparation method of the modified tin dioxide nanoparticles is a chemical coprecipitation method, comprising the following steps: S21. The tin chloride and cerium chloride were added to deionized water and stirred to dissolve to obtain a mixed solution; S22. Slowly adding aqueous ammonia to the mixed solution until pH = 9.5 and stirring to obtain a uniformly dispersed Ce / Sn co-precipitated hydroxide; S23. The resulting reactant is filtered, washed, dried, ground and calcined to obtain Ce-doped tin dioxide nanoparticles; In step S21, the Ce / Sn molar ratio is 1:3.5; The calcination temperature in step S23 is 770°C; The method for preparing the rubber particles comprises the following steps: S1. Mixing: EPDM rubber and EPDM rubber were placed on an open mill and mixed for 1 min, polyaniline doped with modified tin dioxide nanoparticles was added in proportion and mixed for 3 min, stearic acid, zinc oxide, antioxidant RD, diisostyrene peroxide and paraffin oil were added and mixed for 2 min, the mixing temperature was 75 ° C, and a mixed rubber was obtained; S2. Vulcanization: The mixed rubber is placed in a vulcanizer for vulcanization at a vulcanization temperature of 175°C to obtain vulcanized rubber; S3. Molding: Put the vulcanized rubber into an extruder at an extrusion temperature of 85°C, cut and collect after extrusion to obtain rubber particles. Comparative Example 3: A rubber particle comprising the following components by weight: EPDM rubber: 58 parts; EPDM rubber: 42 parts; Porous polyaniline doped with tin dioxide nanoparticles: 46 parts; Stearic acid: 1.4 parts; Zinc oxide: 5.5 parts; Diisopropyl peroxide: 2.5 parts; Antiaging agent RD: 1.5 parts; Paraffin oil: 9 parts; The method for preparing the porous polyaniline doped with tin dioxide nanoparticles comprises the following steps: S11. Adding tin dioxide nanoparticles to water and performing ultrasonic dispersion to obtain a uniform aqueous dispersion; S12. The aniline monomer is dissolved in toluene as the oil phase, the aqueous dispersion is used as the aqueous phase, the aqueous phase and the oil phase are mixed, and emulsified with a high-speed emulsifier to obtain an emulsion; S13. The emulsion was diluted with deionized water, ammonium persulfate was dissolved in a hydrochloric acid solution, both were placed in an ice water bath, the hydrochloric acid solution containing ammonium persulfate was slowly dripped into the emulsion, and the ice water bath was maintained until the reaction was completed; S14. dialyzing the reaction product and freeze-drying it to obtain porous polyaniline doped with tin dioxide nanoparticles; In step S13, the molar ratio of aniline monomer to ammonium persulfate is 1:0.8; The volume percentage of the tin dioxide nanoparticles in the porous polyaniline doped with tin dioxide nanoparticles is 76%; The method for preparing the rubber particles comprises the following steps: S1. Mixing: EPDM rubber and EPDM rubber were placed on an open mill and mixed for 2 min, porous polyaniline doped with tin dioxide nanoparticles was added in proportion and mixed for 2 min, stearic acid, zinc oxide, antioxidant RD, diisostyrene peroxide and paraffin oil were added and mixed for 3 min, the mixing temperature was 95 ° C, and a mixed rubber was obtained; S2. Vulcanization: The mixed rubber is placed in a vulcanizer for vulcanization at a vulcanization temperature of 180°C to obtain a vulcanized rubber; S3. Molding: Put the vulcanized rubber into an extruder at an extrusion temperature of 95°C, cut and collect after extrusion to obtain rubber particles. Comparative Example 4: A rubber particle comprising the following components by weight: EPDM rubber: 100 parts; Porous polyaniline doped with modified tin dioxide nanoparticles: 32 parts; Stearic acid: 0.6 parts; Zinc oxide: 4.7 parts; Diisopropyl peroxide: 3.3 parts; Antiaging agent RD: 1.3 parts; Paraffin oil: 10 parts; The method for preparing the porous polyaniline doped with modified tin dioxide nanoparticles comprises the following steps: S11. The modified tin dioxide nanoparticles are added to water and ultrasonically dispersed to obtain a uniform aqueous dispersion; S12. The aniline monomer is dissolved in toluene as the oil phase, the aqueous dispersion is used as the aqueous phase, the aqueous phase and the oil phase are mixed, and emulsified with a high-speed emulsifier to obtain an emulsion; S13. The emulsion was diluted with deionized water, ammonium persulfate was dissolved in a hydrochloric acid solution, both were placed in an ice water bath, the hydrochloric acid solution containing ammonium persulfate was slowly dripped into the emulsion, and the ice water bath was maintained until the reaction was completed; S14. dialyzing the reaction product and freeze-drying it to obtain porous polyaniline doped with modified tin dioxide nanoparticles; In step S13, the molar ratio of aniline monomer to ammonium persulfate is 1:1.2; The volume proportion of the modified tin dioxide nanoparticles in the porous polyaniline doped with modified tin dioxide nanoparticles is 81%; the modified tin dioxide nanoparticles are Ce-doped tin dioxide nanoparticles; The preparation method of the modified tin dioxide nanoparticles is a chemical coprecipitation method, comprising the following steps: S21. The tin chloride and cerium chloride were added to deionized water and stirred to dissolve to obtain a mixed solution; S22. Slowly adding aqueous ammonia to the mixed solution until pH = 10 and stirring to obtain a uniformly dispersed Ce / Sn co-precipitated hydroxide; S23. The resulting reactant is filtered, washed, dried, ground and calcined to obtain Ce-doped tin dioxide nanoparticles; In step S21, the molar ratio of Ce / Sn is 1:2.5; The calcination temperature in step S23 is 780°C; The method for preparing the rubber particles comprises the following steps: S1. Mixing: The EPDM rubber was placed on an open mill and mixed for 1 min, and the porous polyaniline doped with modified tin dioxide nanoparticles was added in proportion and mixed for 3 min, and stearic acid, zinc oxide, antioxidant RD, diisostyrene peroxide and paraffin oil were added and mixed for 2 min, and the mixing temperature was 80 ° C to obtain a mixed rubber; S2. Vulcanization: The mixed rubber is placed in a vulcanizer for vulcanization at a vulcanization temperature of 170°C to obtain a vulcanized rubber; S3. Molding: Put the vulcanized rubber into an extruder at an extrusion temperature of 115°C, cut and collect after extrusion to obtain rubber particles. The examples and comparative examples were made into standard size samples, and their hardness, tensile strength and elongation at break were tested using a Shore A durometer and a universal testing machine, respectively. Their resistance values were also tested, and their volume resistivity was calculated. The results are shown in the table. In summary, the present invention adds porous polyaniline doped with modified tin dioxide nanoparticles into rubber to prepare pressure-sensitive conductive rubber particles. Compared with the comparative example, the present invention has good conductivity, higher hardness and tensile strength, and excellent comprehensive performance.
Claims
1. A pressure-sensitive conductive rubber particle, characterized in that: The pressure-sensitive conductive rubber particles include the following components by weight: EPDM rubber: 50-60 parts; EPDM rubber: 40-50 parts; Porous polyaniline doped with modified tin dioxide nanoparticles: 30-60 parts; Stearic acid: 0.5-1.5 parts; Zinc oxide: 4-6 parts; Diisopropyl peroxide: 2-4 parts; Antiaging agent RD: 1-2 parts; Paraffin oil: 8-10 parts.
2. The pressure-sensitive conductive rubber particles according to claim 1, characterized in that: The method for preparing the porous polyaniline doped with modified tin dioxide nanoparticles comprises the following steps: S11. The modified tin dioxide nanoparticles are added to water and ultrasonically dispersed to obtain a uniform aqueous dispersion; S12. The aniline monomer is dissolved in toluene as the oil phase, the aqueous dispersion is used as the aqueous phase, the aqueous phase and the oil phase are mixed, and emulsified with a high-speed emulsifier to obtain an emulsion; S13. The emulsion was diluted with deionized water, ammonium persulfate was dissolved in a hydrochloric acid solution, both were placed in an ice water bath, the hydrochloric acid solution containing ammonium persulfate was slowly dripped into the emulsion, and the ice water bath was maintained until the reaction was completed; S14. The reaction product is dialyzed and freeze-dried to obtain porous polyaniline doped with modified tin dioxide nanoparticles.
3. The pressure-sensitive conductive rubber particles according to claim 2, characterized in that: In step S13, the molar ratio of the aniline monomer to ammonium persulfate is 1:0.8-1.
2.
4. The pressure-sensitive conductive rubber particles according to claim 1, characterized in that: The volume proportion of the modified tin dioxide nanoparticles in the porous polyaniline doped with modified tin dioxide nanoparticles is 75-85%.
5. The pressure-sensitive conductive rubber particles according to claim 1, characterized in that: The modified tin dioxide nanoparticles are Ce-doped tin dioxide nanoparticles.
6. The pressure-sensitive conductive rubber particles according to claim 1, characterized in that: The preparation method of the modified tin dioxide nanoparticles is a chemical coprecipitation method, comprising the following steps: S21. The tin chloride and cerium chloride were added to deionized water and stirred to dissolve to obtain a mixed solution; S22. Slowly adding aqueous ammonia to the mixed solution until pH = 9 to 10 and stirring to obtain a uniformly dispersed Ce / Sn co-precipitated hydroxide; S23. The obtained reactant is filtered, washed, dried, ground and calcined to obtain Ce-doped tin dioxide nanoparticles.
7. The pressure-sensitive conductive rubber particles according to claim 6, characterized in that: In the step S21, the molar ratio of Ce / Sn is 1:2.5-4.
8. The pressure-sensitive conductive rubber particles according to claim 6, characterized in that: The calcination temperature in step S23 is 750-800°C.
9. The method for preparing pressure-sensitive conductive rubber particles according to claim 1, characterized in that: The following steps are involved: S1. Mixing: The EPDM rubber and the EPDM rubber are placed on an open mill for mixing, the porous polyaniline doped with modified tin dioxide nanoparticles is added in proportion, stearic acid, zinc oxide, antioxidant RD, diisostyrene peroxide and paraffin oil are added and mixed evenly to obtain a mixed rubber; S2. Vulcanization: Put the mixed rubber into a vulcanizer for vulcanization to obtain vulcanized rubber; S3. Molding: Put the vulcanized rubber into an extruder, cut and collect it after extrusion to obtain pressure-sensitive conductive rubber particles.